Facial growth in patients with isolated cleft palate treated with minimal incision technique compared to a normal population—a cephalometric study at 10 and 16 years of age. (13th November 2019) - Parikakis, Konstantinos; Larson, Ola; Karsten, Agneta
Summary: Objective: To evaluate the result of a novel palatoplasty (minimal incision technique) for closure of an isolated cleft palate (ICP) at 10 and 16 years of age, concerning facial growth, compared to a normal population. Subjects: Treated group: 55 non-syndromic Caucasian children born with an ICP between 1987 and 2001. The children were treated surgically with a one-stage palatoplasty at a mean age of 13 months. Control group: 110 Caucasian children with normal occlusion with no history of clefts or orthodontic intervention. Method: The treated children (25 boys, 30 girls) were matched (gender and age) with the children in the control group. A retrospective evaluation at 10 (mean 10.5) and 16 (mean 16.0) years of age was performed by analysis of lateral cephalograms. Fifteen variables were evaluated. Ninety-nine per cent confidence intervals were calculated. Two-way factorial ANOVA and mixed-model analysis were performed. Results: Treated patients compared to the control group showed: at 10 years of age, smaller mandible ( P = 0.001) and reduced posterior upper and total face heights ( P ≤ 0.001); at 10 and 16 years of age, a retrognathic ( P ≤ 0.001), smaller ( P ≤ 0.006) and with an increased posterior inclination of the maxilla ( P < 0.001), as well as a retrognathic mandible ( P ≤ 0.006). Conclusion: The craniofacial morphology at 10 and 16 years of age in patients born with an ICP and treated with the minimal incision technique differs compared to the morphology of a normal control group born without a cleft. Retrognathic maxillas and a smaller and posteriorly inclined maxilla were found in the treated group.